In whom do we trust? The level and radius of social trust among sport club members. (June 2020) - Burrmann, Ulrike; Braun, Sebastian; Mutz, Michael
This paper refers to the widespread notion that voluntary (sport) organizations produce social capital, popularized through the works of Robert D. Putnam, and compares social trust levels of sport club members with members in other voluntary associations and non-members. We differentiate between in-group trust and out-group trust, highlighting that not only the level of trust but also the "trust radius" counts for social cohesion in modern societies. Refining Putnam's claims, we argue that social trust among members varies with the quality and intensity of participation captured (for instance, through volunteering), diverse social contacts and the level of membership trust experienced in an association. Based on a nation-wide survey, carried out in Germany during 2017/2018, it is demonstrated that members of civic associations indicate higher levels of trust towards in-groups and out-groups compared to non-members and they regard present society as more solidary and trusting. A fine-grained analysis among members of associations further shows that increased trust is typical for volunteers and individuals in socially diverse associations which, at the same time, are characterized by high levels of membership trust. We conclude that sports clubs need to provide beneficial context conditions for producing high levels and a wider radius of trust.